2021
DOI: 10.1017/jfm.2021.114
|View full text |Cite
|
Sign up to set email alerts
|

On the criteria of large cavitation bubbles in a tube during a transient process

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…The tube-arrest setup used in the research is adapted from previous research of the authors [8] and is schematically presented in figure 1. A conical-frustum shaped acrylic tube filled with deionized water is driven upwards by stepping on the actuator until it hits on the buffer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tube-arrest setup used in the research is adapted from previous research of the authors [8] and is schematically presented in figure 1. A conical-frustum shaped acrylic tube filled with deionized water is driven upwards by stepping on the actuator until it hits on the buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical simulations supported by experimental indicate that the oscillation period and size of the cavitation bubble are related to the initial flow velocity [3,4]. At the laboratory setup, the tube-arrest method has been used to produce the transient cavitation bubbles in a cylindrical tube [6,7,8]. The results suggest that the size of the bubble is related to the velocity of the tube [6,7] and a Rayleigh-type model for the dynamics of the large bubble is put forward [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the destructive nature of the phenomena 5,6,18 , systematical experimental studies using circulating pipe system remain difficult and limited. In contrast, the so-called 'tube-arrest' method provides an equivalent and low-cost experimental technique for the study of cavitation bubbles during the transient process [19][20][21] . In a tube-arrest setup, a tube filled with liquid is driven upwards until it impacts with a buffer, causing rapid liquid deceleration and inducing cavitation bubbles at the bottom of the tube.…”
Section: Introductionmentioning
confidence: 99%
“…In a tube-arrest setup, a tube filled with liquid is driven upwards until it impacts with a buffer, causing rapid liquid deceleration and inducing cavitation bubbles at the bottom of the tube. Based on the experiments in a tube-arrest apparatus, Xu et al 21 proposed the onset criteria of large cavitation bubbles generated at the close end of the cylindrical tube. They found that the large cylindrical bubbles collapse at a finite speed, and the collapse time can be estimated by a newly established Rayleigh-type model.…”
Section: Introductionmentioning
confidence: 99%